Geomorphological Analysis of the Right Bank Area of Bulango Ulu Dam, Gorontalo Province Using Geological and DEM-Based Terrain Evaluation - Suma, Muhamad Danial; Arifin, Yayu Indriati; Akase, Noviar (Jambura Geoscience Review, 2025)
This study investigates the geomorphological characteristics of the right bank area of the Bulango Ulu Dam in Gorontalo Province to support infrastructure planning, risk assessment, and sustainable land use. Employing integrated methods involving field observations and Digital Elevation Model (DEM) analysis, the research identifies two principal geomorphological units: Structural Low Hills (S1) and Fluvial Plains (F1). These units are shaped by the combined influence of endogenic processes, such as tectonic uplift and structural deformation, and exogenic processes, including fluvial erosion, sedimentation, and weathering. Lithological analysis revealed the presence of three main rock units diorite, granodiorite, and alluvial deposits each contributing to the area's terrain diversity and physical stability. Morphometric classification indicates that steep (30–70%) and very steep (70–140%) slopes dominate more than half of the study area, highlighting a high susceptibility to landslides and erosion hazards, particularly during peak rainfall seasons. The identification of a sub-dendritic drainage pattern suggests that geological structures play a vital role in directing surface runoff and sediment transport. The novelty of this research lies in its localized and detailed geomorphological assessment, which had not been previously conducted on the dam’s right bank. The findings have practical implications for dam safety, slope reinforcement strategies, and regional spatial planning under dynamic geological conditions.